2017
DOI: 10.3389/fnins.2017.00462
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Prefrontal Theta Burst Stimulation on Clinical Neuropsychological Tasks

Abstract: Theta burst stimulation (TBS) protocols hold high promise in neuropsychological rehabilitation. Nevertheless, their ability to either decrease (continuous, cTBS) or increase (intermittent, iTBS) cortical excitability in areas other than the primary motor cortex, and their consistency modulating human behaviors with clinically relevant tasks remain to be fully established. The behavioral effects of TBS over the dorsolateral prefrontal cortex (dlPFC) are particularly interesting given its involvement in working … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
25
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 96 publications
6
25
2
Order By: Relevance
“…The reason for this discrepancy remains unclear, and further research is required as currently only a few studies have been performed in this area to date (Cheng et al, ; Debarnot et al, ; Demeter, Mirdamadi, Meehan, & Taylor, ; Hoy et al, ; Ryals, Rogers, Gross, Polnaszek, & Voss, ). A recent study investigated the effect of prefrontal TBS on a series of cognitive tasks, such as Digits Backward, 3‐back task, Stroop Colour and Word Test, and the Tower of Hanoi (Viejo‐Sobera et al, ). Only subtle behavioural changes were found in these measures in the absence of statistical differences between iTBS, cTBS and sham condition, and with no clear bi‐directional changes (i.e., enhanced or impaired performance following iTBS or cTBS, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…The reason for this discrepancy remains unclear, and further research is required as currently only a few studies have been performed in this area to date (Cheng et al, ; Debarnot et al, ; Demeter, Mirdamadi, Meehan, & Taylor, ; Hoy et al, ; Ryals, Rogers, Gross, Polnaszek, & Voss, ). A recent study investigated the effect of prefrontal TBS on a series of cognitive tasks, such as Digits Backward, 3‐back task, Stroop Colour and Word Test, and the Tower of Hanoi (Viejo‐Sobera et al, ). Only subtle behavioural changes were found in these measures in the absence of statistical differences between iTBS, cTBS and sham condition, and with no clear bi‐directional changes (i.e., enhanced or impaired performance following iTBS or cTBS, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…However, several studies with large sample sizes (n > 50) have found no group-level change in MEPs following 50 Hz iTBS (Hamada et al, 2013;Lopez-Alonso et al, 2014;Player, Taylor, Alonzo, & Loo, 2012). Similarly, prefrontal iTBS has shown an improvement in working memory in some studies Lowe et al, 2018), however, not in other studies (Chung, Rogasch, Hoy, Sullivan, et al, 2018b;Grossheinrich et al, 2009;Viejo-Sobera et al, 2017). Similarly, prefrontal iTBS has shown an improvement in working memory in some studies Lowe et al, 2018), however, not in other studies (Chung, Rogasch, Hoy, Sullivan, et al, 2018b;Grossheinrich et al, 2009;Viejo-Sobera et al, 2017).…”
Section: Effect Of Individualised Itbs On Plastic Effects In the Prmentioning
confidence: 98%
“…Evidence suggests TBS over the prefrontal cortex may also modulate executive functioning in healthy individuals (Cho et al, 2010;Verbruggen, Aron, Stevens, & Chambers, 2010;Viejo-Sobera et al, 2017). Evidence suggests TBS over the prefrontal cortex may also modulate executive functioning in healthy individuals (Cho et al, 2010;Verbruggen, Aron, Stevens, & Chambers, 2010;Viejo-Sobera et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations